Vitamin C New Biochemical and Functional Insights - Chen, Qi; Vissers, Margreet C.M (Taylor & Francis, 2020)
Vitamin C holds a unique place in scientific and cultural history. In this book, a group of leading scientific researchers describe new insights into the myriad ways vitamin C is employed during normal physiological functioning. In addition, the text provides an extensive overview of the following: the rationale for utilizing vitamin C in the clinic, updates on recent uses of vitamin C in cancer treatment through high-dose intravenous therapies, the role vitamin C plays in the treatment of sepsis and infectious disease, management of the ways vitamin C can improve stem cell differentiation, as well as vitamin C use in other important health situations.